Discovery of clinical candidate Sivopixant (S-600918): Lead optimization of dioxotriazine derivatives as selective P2X3 receptor antagonists. (15th November 2021) - Kai, Hiroyuki; Horiguchi, Tohru; Kameyma, Takayuki; Onodera, Naohiro; Itoh, Naohiro; Fujii, Yasuhiko; Ichihashi, Yusuke; Hirai, Keiichiro; Shintani, Takuya; Nakamura, Kenichiroh; Minami, Kazuhisa; Kasai, Erika; et al.
Graphical abstract: Abstract: In previous work, we discovered a lead compound and conducted initial SAR studies on a novel series of dioxotriazines to identify the compound as one of the P2X3 receptor antagonists. This compound showed high P2X3 receptor selectivity and a strong analgesic effect. Although not selected for clinical development, the compound was evaluated from various aspects as a tool compound. In the course of the following study, the molecular structures of the dioxotriazines were modified based on pharmacokinetic/pharmacodynamic (PK/PD) analyses. As a result of these SAR studies, Sivopixant (S-600918) was identified as a clinical candidate with potent and selective antagonistic activity (P2X3 IC50, 4.2 nM; P2X2/3 IC50, 1100 nM) and a strong analgesic effect in the rat partial sciatic nerve ligation model (Seltzer model) of allodynia (ED50, 0.4 mg/kg).